2009
DOI: 10.1016/j.jbiomech.2009.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Growth plate mechanics and mechanobiology. A survey of present understanding

Abstract: The longitudinal growth of long bones occurs in growth plates where chondrocytes synthesize cartilage that is subsequently ossified. Altered growth and subsequent deformity resulting from abnormal mechanical loading is often referred to as mechanical modulation of bone growth. This phenomenon has key implications in the progression of infant and juvenile musculoskeletal deformities, such as adolescent idiopathic scoliosis, hyperkyphosis, genus varus/valgus, tibia vara/ valga, as well as neuromuscular diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
165
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(174 citation statements)
references
References 73 publications
(138 reference statements)
3
165
2
4
Order By: Relevance
“…Starting at the epiphyseal end of the growth plate, the flat and small chondrocytes (reserve zone) activate and start to proliferate (proliferative zone), thereafter growing in size (hypertrophic zone) toward the metaphysic, ultimately resulting in chondrocyte apoptosis, blood vessel invasion into the extracellular matrix, and finally ossification into bone tissue. (8,9) We hypothesized that markers reflecting cartilage or bone metabolism are also potential surrogates for catch-up growth in preterm infants.…”
mentioning
confidence: 99%
“…Starting at the epiphyseal end of the growth plate, the flat and small chondrocytes (reserve zone) activate and start to proliferate (proliferative zone), thereafter growing in size (hypertrophic zone) toward the metaphysic, ultimately resulting in chondrocyte apoptosis, blood vessel invasion into the extracellular matrix, and finally ossification into bone tissue. (8,9) We hypothesized that markers reflecting cartilage or bone metabolism are also potential surrogates for catch-up growth in preterm infants.…”
mentioning
confidence: 99%
“…Hypertrophy (changes in cell volume and height), proliferation of chondrocytes as well as matrix synthesis have been implicated as the most important factors in both normal and mechanically modulated growth of long bones. 1,[12][13][14][15][16] It has been suggested that the final volume and shape of hypertrophic chondrocytes are important factors in determining the rate of longitudinal bone growth. The several-fold chondrocytic hypertrophy is believed to contribute to the major portion of long bone growth, with the remainder due to matrix synthesis in proliferative and hypertrophic zones as well as chondrocyte proliferation.…”
mentioning
confidence: 99%
“…The several-fold chondrocytic hypertrophy is believed to contribute to the major portion of long bone growth, with the remainder due to matrix synthesis in proliferative and hypertrophic zones as well as chondrocyte proliferation. 6,10,11,14,15,17,18 According to Hunziker and Schenk, 6 the normal growth process of long bones is mostly controlled by the morphometric modulation of chondrocyte phenotype. A strong linear relationship was indeed established between hypertrophic chondrocytes volume and longitudinal bone growth rate in both tibial and radial growth plates of three animal species (rats, mice, and pigs).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Strong evidence also suggests that excessive tensile strain leads to direct injury to the alveolar epithelium, in addition to the biochemical responses of cells [11][12][13][14] . Although the focus here is primarily on the response of lung cells to mechanical deformation, pathways induced by mechanotransduction play a key role in the basic function of many tissues in the human body, including the regulation of vascular tone 15 and the development of the growth plate 16 .…”
Section: Introductionmentioning
confidence: 99%